PENGARUH VARIASI CAMPURAN PAKAN ( KOTORAN AYAM DAN AMPAS TAHU) DAN LAMA FERMENTASI TERHADAP BIOMASSA CACING SUTRA (Tubifex sp) - sari, rima; Santoso, Handoko; Achyani, Achyani (BIOLOVA, 2021)
Abstract: This study aims to determine the effect of various feed mixtures and fermentation time on silkworm biomass. The method used is an experimental method using a completely randomized design (CRD). The treatment in this study was the provision of a mixture of chicken manure and tofu dregs with a mixture of A = 50% tofu dregs mixture of chicken manure 50% B = 100% tofu dregs mixture of chicken manure. C = 75% chicken manure mixture to 25% tofu dregs. D = 25% chicken manure mixture to 75% tofu dregs. E = 0% chicken manure mixture 100% tofu dregs. The parameters measured in this study were silkworm biomass, with supporting data in the form of water temperature and pH. The data obtained were tabulated and analyzed by Two Ways Analysis Of Variance (ANOVA) or TWO WAY ANOVA. Based on the results of the analysis, the sig. 0.005. eISSN 2716-473X p ISSN 2716-4748 Received: September 2020 Approved: Published: 2 Because of the sig. 0.005 from α 0.05, then H0 is accepted, which means there is no difference in silkworm biomass between A, B, C, D, and E, the variation in feed and fermentation time of 6 days and 10 days has no effect on the biomass of silk worms. The temperature obtained during the study ranged from 27º-28º, while the pH obtained during the study was 6-7. Keywords: Chicken Manure, Tofu Dregs, Fermentation, Biomass, Silk worm